1977
DOI: 10.1002/ajpa.1330460119
|View full text |Cite
|
Sign up to set email alerts
|

The effect of artificial cranial deformation on the incidence of wormian bones in the lambdoidal suture

Abstract: One hundred and twenty adult and 80 human fetal skulls were examined to find the relationship (if any) between the presence of wormian bones in the lambdoidal suture and artificial deformation of the skull. Wormian bones occur in deformed and undeformed skulls with no significant differences. Wormian bones detected in fetal skulls preclude cultural deformation as an important factor in the formation of these bones. It is hypothesized that a genetic predisposition (genes allowing formation of secondary ossifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
3

Year Published

1979
1979
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 6 publications
4
66
0
3
Order By: Relevance
“…The developments of the wormian bones occur at an early membranous stage of skull growth and it is difficult to correlate this with brain disorders or relate specifically to any one type. It was also reported that the wormain bones and skull growth are not affected by any mechanical distortion, which is traditional practice in some of the tribal communities [15].…”
Section: Resultsmentioning
confidence: 96%
“…The developments of the wormian bones occur at an early membranous stage of skull growth and it is difficult to correlate this with brain disorders or relate specifically to any one type. It was also reported that the wormain bones and skull growth are not affected by any mechanical distortion, which is traditional practice in some of the tribal communities [15].…”
Section: Resultsmentioning
confidence: 96%
“…5 However, El-Najjar and Dawson, in 1977, on comparing the prevalence of wormian bones in deformed and undeformed skulls of Southwestern Native Americans, concluded that no significant difference exists between these two groups. 9 They proposed that artificial cranial deformation does not influence the prevalence of wormian bones but affects the number of these bones when they are present. 9 …”
Section: Consequence Of Skull Deformationmentioning
confidence: 99%
“…9 They proposed that artificial cranial deformation does not influence the prevalence of wormian bones but affects the number of these bones when they are present. 9 …”
Section: Consequence Of Skull Deformationmentioning
confidence: 99%
“…In 1977, El-Najjar and Dawson concluded this theory by comparing the incidence of wormian bones between skulls with deformities and those without [13], and supported the existence of both environmental as well as genetic factors in its formation [14]. Bergman et al in 1988 [15] suggested that development of wormian bones could possibly may develop due to the rapid cranial expansion that spreads sutures apart and develops dural strain within the sutures and fontanelles.…”
Section: Resultsmentioning
confidence: 99%